2015
DOI: 10.1007/s11552-014-9734-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dominant Limb Involvement on DASH and QuickDASH

Abstract: Prognostic level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…The authors highlighted the role of psychological factors in perceived disability. We agree with Kachooei et al 15 and other authors 16 19 who have investigated the role of psychological factors on patient-reported disability measures. We feel that better coping ability and adaptation to musculoskeletal disability would overpower the pain and functional disturbances arising from involvement of the dominant arm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The authors highlighted the role of psychological factors in perceived disability. We agree with Kachooei et al 15 and other authors 16 19 who have investigated the role of psychological factors on patient-reported disability measures. We feel that better coping ability and adaptation to musculoskeletal disability would overpower the pain and functional disturbances arising from involvement of the dominant arm.…”
Section: Discussionsupporting
confidence: 92%
“…Edelmann et al 14 found no differences in DASH scores in patients after proximal humerus fracture when the dominant limb was involved. In a study by Kachooei et al, 15 dominant hand involvement, trauma, shoulder involvement, and female sex were associated with significantly higher DASH scores, but accounted for only 10% of the variability in scores which may not be clinically significant. The authors highlighted the role of psychological factors in perceived disability.…”
Section: Discussionmentioning
confidence: 90%
“…5 The only factor influencing the updated Quick DASH questionnaire but not the standard Quick DASH was affected side, suggesting that either hand can be used for modern activities. 12 However, pain interference was the only factor independently associated with scores on both questionnaires in multivariable analysis. The observation of no correlation between age and the modern Quick DASH score suggests that younger subjects were not more affected by technology than older subjects as might be assumed.…”
Section: Discussionmentioning
confidence: 88%
“…Using DASH scores at presentation, studies of thumb arthritis and surgical shoulder conditions suggest similar degrees of functional impairment 2124 . However, others have found a significant difference between shoulder and hand populations with the hand population reporting better function by an average of 14 points on the DASH 17,25 . Within our study population, patients presenting with hand conditions reported better average function than patients with shoulder conditions.…”
Section: Discussionmentioning
confidence: 96%